The dynamics of intergenerational closure and family networks of social cohesion - Windzio, Michael; Kaminski, Patrick (Frontiers in Sociology, 2023)
We investigate the correlation of ties among school-children’s parents with violence in schools, and two mechanisms of intergenerational closure (IC). Coleman described ties among parents of befriended children as IC. Until now, IC indicated social capital in schools and neighborhoods, but existing evidence is rather ambiguous and does not utilize network data. According to ‘top-down’ IC, children establish network ties because of the acquaintance among their parents. ‘Bottom-up’ IC implies that children make friends first and then their parents get involved. We use longitudinal social network data from k=10 school classes and N=238 adolescents and disentangle the two different dynamics of IC by applying Bayesian stochastic actor-oriented models (SAOMs) for network evolution. SAOMs show positive ‘top-down’ and ‘bottom-up’ effects on IC, with the latter being considerably stronger.